Comprehensive Approach to Developing Baseline Reference Ranges for Platelet Function - Olga B. Gordeeva; Maria S. Karaseva; Vasily A. Lastovka; Nato D. Vashakmadze; Margarita A. Soloshenko; Gregory V. Revunenkov; Kirill A. Valyalov; Viktor V. Altunin (Педиатрическая фармакология)
Background. Thrombocytopathies are topical issues of pediatrics. Platelet dysfunction clinically manifests as thrombotic and hemorrhagic events of various severity and location. Platelet function can be evaluated via aggregatometry. Specified parameters for aggregatometry can be used in pediatrics as a standard for evaluating platelet function in peripheral blood. There were no similar studies in children in Russian Federation.Objective. The aim of the study is — to justify the significance of reference ranges (RR) development for platelet aggregatometry in pediatrics.Methods. The study included 30 relatively healthy patients aged from 1 to 18 years. Laboratory tests included complete blood count via automatic hematological analyzer; platelet aggregation in whole blood was evaluated via impedance aggregometer; plasmic hemostasis component (Quick prothrombin), activated partial thromboplastin time (APTT), thrombin time (TT), and fibrinogen were evaluated on automatic coagulation analyzer; molecular genetic study of platelet genes polymorphisms was performed via real-time PCR. Several inducers were used to study platelet aggregation: thrombin receptor activating peptide (TRAP), adenosine diphosphate (ADP), arachidonic acid (ASPI). Instrumental methods included electrocardiography, ultrasound of abdomen, urinary system, and thyroid gland.Results. The study included 16 girls and 14 boys. The median age was 9.4, interquartile range (IQR) was 6.5; 14,1. RR for platelet aggregation indicators were determined for all aggregation inducers (thrombin, ADP, arachidonic acid) as a result of the study.Conclusion. The obtained data will allow to improve the diagnosis approach for platelet dysfunction regarding the established reference ranges. The results of further research may contribute in the development of the algorithm for controlling antiplatelet therapy in patients with contraindications or with genetically determined low sensitivity to thrombocyte aggregation inhibitors based on acetylsalicylic acid.